The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.52825/bis.v1i.41
|View full text |Cite
|
Sign up to set email alerts
|

Stream Processing Tools for Analyzing Objects in Motion Sending High-Volume Location Data

Abstract: Recently we observe a significant increase in the amount of easily accessible data on transport and mobility. This data is mostly massive streams of high velocity, magnitude, and heterogeneity, which represent a flow of goods, shipments and the movements of fleet. It is therefore necessary to develop a scalable framework and apply tools capable of handling these streams. In the paper we propose an approach for the selection of software for stream processing solutions that may be used in the transportation doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Later in 2021, Krzysztof Wecel et al [ 32 ] selected six frameworks, but has chosen to focus their analysis on comparing Spark and Flink. They concluded that Spark is more memory efficient while Flink is more CPU efficient.…”
Section: Big Data Stream Processing Frameworkmentioning
confidence: 99%
“…Later in 2021, Krzysztof Wecel et al [ 32 ] selected six frameworks, but has chosen to focus their analysis on comparing Spark and Flink. They concluded that Spark is more memory efficient while Flink is more CPU efficient.…”
Section: Big Data Stream Processing Frameworkmentioning
confidence: 99%